Metronidazole 0.75% gel vs. ketoconazole 2% cream in the treatment of facial seborrheic dermatitis: a randomized, double-blind study - (:unkn) unknown (BLACKWELL PUBLISHING, 2007)
Background Recently, two placebo-controlled studies have shown that topical metronidazole was effective in the treatment of seborrheic dermatitis. Objective To compare the efficacy and safety of metronidazole 0.75% gel with that of ketoconazole 2% cream in the treatment of facial seborrheic dermatitis. Methods A total of 60 consecutive patients with facial seborrheic dermatitis were included. Patients were randomized into two groups. One group used ketoconazole 2% cream with metronidazole gel as vehicle; the other group used metronidazole 0.75% gel with ketoconazole cream as vehicle for a 4-week treatment period. Main outcome measures were change in clinical severity scores, patients' and investigator's global evaluation of improvement and frequency of side-effects. Results All the assessments were made by an investigator who was unaware of which group the patients were allocated to. Mean percentage decrease in clinical severity scores from baseline to last available visit was 63.4% (95% CI 57.7-69) and 54.4% (95% CI 47.9-61) in the ketoconazole- and metronidazole-treated patients, respectively (P = 0.31). Eighty-two per cent of patients in the ketoconazole group vs. 79% of patients in the metronidazole group rated their global improvement as significant or moderate (P > 0.05). No statistically significant difference in the frequency of side-effects was detected between the two groups. The results of this study need to be confirmed in further studies involving large numbers of patients. Conclusion Our data demonstrated that metronidazole 0.75% gel had a comparable efficacy and safety profile with that of ketoconazole 2% cream in the treatment of facial seborrheic dermatitis.
Keywords: ketoconazole; metronidazole; seborrheic dermatitis; treatment; TOPICAL METRONIDAZOLE